Doing Research in Aotearoa: A Pākehā Exemplar of the Application of the Te Ara Tika Ethical Framework - Came, H (Taylor & Francis, 2013)
Kaupapa Māori was once and still is for some ordinary in the context of Aotearoa. Active processes of colonisation and assimilation led by the settler government in New Zealand have served to significantly displace Māori to the marginalised position of exotic and other. Te Ara Tika powerfully reaffirms Māori experience as ordinary, embeds Te Tiriti o Waitangi and core western ethical principles into a framework uniquely of this land. Within this paper I share my application of this framework as an exemplar for others to benchmark against and critique. I conclude by advocating for the uptake of Te Ara Tika framework by Tauiwi (non-Māori) researchers as a response to the challenge from Māori to do acceptable, accountable and responsible research.
Keywords: Kaupapa Māori; Public health research; Treaty of Waitangi; Te Tiriti o Waitangi; Research ethics; Institutional racism